Modelling the coordinated supply chain network - M. E. Seliaman; Ab Rahman Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2010)
A supply chain is a network of suppliers, manufactures, distributors and retailers that deliver finished products to the end customers. The configuration of the manufacturing and distribution facilities, and selection of distribution channels are typical strategic supply chain decisions. In this paper we consider the problem of reconfiguring the supply chain network to significantly improve customer service levels and reduce system wide cost. For this purpose we develop a mathematical model that can help in the integrated design of strategic supply chain networks and the determination of tactical production-inventory decisions. In this model, inventory and production cycles are assumed synchronised across the entire supply chain. Then we describe an optimal solution procedure for solving the model and present a numerical example for illustrating the model. The numerical results show that the network configuration under integer multipliers coordination mechanism will result in lower total cost